Brolucizumab and platelet activation and reactivity - Sobolewska, Bianka Weronika; Poeschel, S.; Kalbacher, H.; Zieber, K.; Paczulla Stanger, A. M.; Stellos, Konstantinos; Ziemssen, F. (Current eye research, 2025)
This study explores the potential interaction of brolucizumab with platelets and its effects on platelet activation and reactivity, crucial in retinal vasculitis and retinal vascular occlusion. Safety concerns remain of interest, although brolucizumab showed superior retinal efficacy and reduced injection frequency compared to other licensed anti-VEGF agents. Resting and activated platelets of healthy volunteers were pretreated with brolucizumab at the following concentrations 0.6 µg/mL, 3 µg/mL, 6 µg/mL, 300 µg/mL, and 3000 µ/mL or its solvent or PBS. The surface expression of platelet activation markers GPIIb/IIIa and P-selectin was determined by multispectral imaging flow cytometry, which combines flow cytometry and fluorescence microscopy. Two different methods were used to examine the interaction of brolucizumab with platelets: 1) A cross-pretreatment experiment was performed with FITC-labeled brolucizumab and bevacizumab; 2) Resting and activated platelets were pretreated with brolucizumab or its solvent or PBS, followed by anti-brolucizumab antibody generated by rabbit immunization. Brolucizumab did not significantly affect platelet activation compared to solvent or PBS, across a range of concentrations. No significant upregulation of CD62P and no activation of the fibrinogen receptor (GPIIb/IIa) were observed in resting and TRAP-activated platelets. After pretreatment with PBS, the level of brolucizumab-FITC was significantly lower in comparison to bevacizumab-FITC (normalized MFI = 3.32, CI = 3.16-3.48 vs. normalized MFI = 7.19, CI = 7.04-7.35; p < 0.001). Both brolucizumab- and bevacizumab-FITC were downregulated after pretreatment with brolucizumab or bevacizumab compared to pretreatment with PBS. Antibodies against brolucizumab did not show any significant difference between pretreatment with brolucizumab and its solvent in resting and TRAP-activated platelets. Brolucizumab does not appear to directly affect platelet activation or reactivity to thrombin receptor agonists. No platelet interaction was observed after increasing brolucizumab concentrations or anti-brolucizumab antibodies in resting and activated platelets. However, brolucizumab might be taken up in platelets.